Study on co-crystal formation of ibuprofen and glutaric acid via slow cooling technique: article / Noradila Mohamed Hanapi and Muhamad Fitri Othman - Hanapi, Noradila Mohamed; Othman, Muhamad Fitri (2017)
Ibuprofen is non-steroidal anti-inflammatory drug (NSAID) that used to treat pain or inflammation and to reduce fever. It is fall under Biopharmaceutical Classification System (BCS) Class II which has low solubility but high permeability. In order to improve the bioavailability of ibuprofen, an engineering approach has been done. For that purpose, an engineering crystal approach is done by preparing the cocrystal of ibuprofen and co-former such as glutaric acid to help in improving drug solubility. The method used to prepare the co-crystal is slow cooling technique. Using this technique, there are several samples of ibuprofen-glutaric acid that successfully to perform co-crystal. The successful samples were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and optical microscope in order to confirm their morphology and purity. The findings from the study shows that the result of FTIR shows that there is new bond formed from the interaction of ibuprofen and glutaric acid. The result from DSC showing that there is formation of new melting point in between pure component used in this experiment. Lastly, the optical microscope had successfully identify the morphology that revealed by the co-crystals.